(untitled) (ELang | An English Language Education Journal, 2016)
The title of the research paper was “The Effectiveness of Songs Used for Teaching Conditional Sentences”. The study was conducted on the 16th of September 2015 until 23rd of September 2015. The objectives of the study were to find out whether or not the songs were effective used for teaching conditional sentences and to find out what were students responses toward the songs. The method that was used in this research was pre-experimental design. There was only one group to be researched. The sample was the second grade students of SMA 1 Majalaya that consists of 41 students. The instruments were test and questionnaire. The research findings were the value of t. was higher than the t. table (19.818 > 2.02). it could be put forward that songs were useful for improving grammatical mastery especially in the first conditional sentences and the second conditional sentences. The Null Hypotheses (H0) was rejected and the Alternative Hypotheses (Ha) was accepted, stating that there was significant difference in the result of students scores before and after the treatment using songs. It can be put forward that the use of songs for teaching conditional sentences to the second grade of SMA 1 Majalaya was effective. Then the writer found out that the students liked being taught conditional sentences by using songs. It was shown by the result of the questionnaire that 89% of students answered that they really liked being taught by using songs. And 94% of students anwered that the atmosphere of the class became enjoyable. Based on the result that has been found by the writer, it can be put forward that songs are effective used for teaching conditional sentences and the students’ responses are good and positive.